Association between fatigue and psychological factors among undergraduate university students: a cross-sectional study - Chan, Zhi Xin (2023)
Background and Objective: Fatigue is common among university students and can affect their academic performance and well-being. Besides, female students often reported higher fatigue levels than male students. High academic demands often lead to stress, anxiety and depression, contributing to physical and mental exhaustion. However, there are limited studies comparing gender on different types of fatigue and investigating the association between fatigue and psychological factors among Malaysian university students. The objectives of this study were to identify the prevalence of different types of fatigue and psychological factors and to compare the different types of fatigue among undergraduate students between genders. Lastly, this study also investigated the association between fatigue and psychological factors among undergraduate students.